1101/ 1102 (1690/ 1691) tarihli 100 numaralı mühimme defteri: transkripsiyonu ve değerlendirilmesi [s.1-145] - Şakar, Muzaffer Fehmi (My University, 2007)
Mühime Defterleri, Dîvân-ı Hümâyûn’da müzâkere edilen hususlar üzerine padisahın onayı alındıktan sonra düzenlenen fermanların sûretlerinin kaydedildigi defterlerdir. Hükümler, devletin merkez ile tasra teskilâtının idârî yapısı ve çalısma sekilleri, imar ve iskan siyasetleri, isyanlar, askerî tarih, iç ve dıs siyaset münasebetlerini içerir. Bu nitelikleri itibârıyla, Osmanlı Devleti’nin siyasî, sosyal, adlî ve ekonomik tarihi üzerine yapılacak arastırmalar için büyük önem tasımaktadırlar. 100 Numaralı Mühime Defteri, 1690/ 1691 yıllarında Belgrad, Vidin, Avlonya gibi kaybedilen Rumeli kasaba ve kalelerinin kurtarılması amacıyla gerekli mühimmat ve askeri tedarik etmeleri için Rumeli seraskerlerine, Erdel Kralına, Eflak Voyvodasına, Türkmen ve Ekrâd boybeylerine yazılmıs nâme ve hükümleri içerir.

Mühimme Inventories are the registrations which include the copies of after the approval of the Padishah arranged fermans related with the matters of discussed in Divan-i Humayun (Council of Imperial). Judgments include administrative structure and working shapes of State’s central and province organization, politics of development and settlement, uprisings, military history and the relations of national and foreign politics. From the point of view of these attributes, these have great importance for the researches will be made in future about political, juridical and economic history of Ottoman Empire. The Mühimme Inventory which numbered by 100 includes ‘name’ (appellations) and judgments which were sent to the Minister of War of Rumelia (that part of the Ottoman Empire which was in Europe) to provide the required military supplies and soldiers with the aim of rescuing the small towns and fortresses of Rumelia like Belgrade, Vidin and Avlonia which were loosed between 1690-1691.
Keywords: Mühimme Defterleri; Yeniçağ Tarihi